THE RELATIONSHIP BETWEEN ENTREPRENEURIAL MINDSET AND THE ADAPTABILITY AND RESILIENCE OF BUSINESS OWNERS DURING ECONOMIC CRISES - Hendrik, Nitaniel; Ala, Helda Marlin; Fanggidae, Herny Constantia; Manafe, Mesri Welhelmina Nisriani (Technopreneurship and Educational Development Review (TENDER), 2024)
This study aims to analyze the relationship between entrepreneurial mindset and the adaptability and resilience of business owners in facing economic crises. Using a qualitative literature review method with descriptive analysis, the research examines 25 selectively chosen articles from a pool of 50 identified through Google Scholar spanning 2001–2024. The findings reveal that an entrepreneurial mindset—characterized by risk-taking, creativity, and opportunity recognition—significantly contributes to the success of business owners in adjusting strategies and enduring economic pressures. Case studies, such as Kopi Kenangan, Rumah Makan Padang Sederhana, and Javara Indonesia, highlight the importance of an entrepreneurial mindset in supporting business adaptability and resilience. However, challenges such as limited access to training and financial constraints remain significant barriers to developing entrepreneurial mindsets among SME owners. This study recommends strengthening entrepreneurial training programs, expanding access to financing, and fostering collaboration among governments, educational institutions, and business owners to enhance SMEs' competitiveness during economic crises.